Preparation of Jam and Jelly using star fruit and assessment of biochemical and organoleptic properties of these value-added products (International Journal of Agricultural Research, Innovation and Technology, 2024)
Making of jam and jelly is the common method of preserving fruit, the main factor being high concentration of sugar that helps in preservation. In Bangladesh, the star fruit (Averrhoa carambola L.) BARI Kamranga-1 is available from September through October and January through February. To obtain the health benefits (anti-inflammatory, analgesic, hypoglycemic, antimicrobial, hepato-protective and anti-ulcer activity) of star fruit throughout the year, jam and jelly products were developed using star fruit. Five jams and five jellies were prepared as value-added products using different ingredients with different combinations. Biochemical properties, chemical analysis, and organoleptic observations of star fruit jam and star fruit jelly were measured to determine the quality of the products and overall public acceptance. The overall acceptability of Jam 2 was the highest, and in case of jelly , Jelly 4 showed the highest score. Additional study is needed to understand better, how star fruit can be processed because there are so many local sorts and variants of the fruit. This will enable us to decide which kinds are most suitable for developing specific goods with the potential to enhance health.Int. J. Agril. Res. Innov. Tech. 14(1): 45-52, June 2024